Application of Augmented Reality (AR) in vocational education: A systematic literature review - Supriyanto Supriyanto; Quienera Joshua; Ade Gafar Abdullah; Emmanuel Obobi Tettehfio; Sulaeman Deni Ramdani (Jurnal Pendidikan Vokasi, 2023)
Augmented Reality (AR) is a technology that combines two-dimensional and or three-dimensional virtual objects into a real environment and then projects these virtual objects in reality in real time. Through this AR technology, users can see virtual objects added to the real world with contextual information. In education, AR has been widely used to complement the standard curriculum. Text, graphics, video, and audio can be superimposed into the student's real-time environment. This article aims to examine how the application and impact of the use of AR in vocational education. The Systematic Literature Review (SLR) method is used to identify, study, evaluate, and interpret Augmented Reality in vocational education. Research data were identified using the SLR method with the help of the PRISMA 2020 form. Article collection was carried out on the Science Direct database. There were as many as 454 articles. After being selected using inclusion and exclusion criteria, the data used were 14 articles. The study results reveal that AR is applied in learning as an innovative learning medium, a new approach to learning to improve students' understanding of knowledge and skills and provide a concrete learning experience. The integration of AR in education has the impact of increasing students' understanding and learning experience, promoting positive attitudes, making the learning process fun and interesting, and learning efficiency